The influence of pacing strategy during short-term maximal exercise - Bellardini, H.; Knutsson, M.; Tonkonogi, M. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
The purpose of this study was to investigate the effects of different pacing strategies on performance in 30, 60 and 300 seconds cycling. Furthermore, the effect of different pacing strategies on the proportion of energy derived from aerobic and anaerobic sources during cycling was studied. Six male competitive cyclists (age 29 (21-35) years, VO2peak 63 (59-72) ml/min/kg body mass and six female subjects who performed cycling on regular basis (age 26 (21-39) years, VO2peak 50 (45-55) ml/min/kg body mass participated in the study. Four different pacing strategies at 30 and 60 seconds (all-out, free chosen, even and spurt) and three different pacing strategies at 300 seconds (free chosen, even and spurt) was performed in different days and in random order. In The all-out strategy the subjects worked at a maximum effort from the beginning and through the whole exercise. During The free chosen strategy the subjects chosen a spontaneous pacing pattern to perform maximal work in the predetermined time. The design of The spurt strategy was to maintain an even pace during the initial 80% of the race time after which the subjects were instructed to spurt and complete as much work as possible. The task during The even strategy was to maintain an even pace through the whole test. The results of this study demonstrate that the pacing strategy has substantial effect on performance during 30, 60 and 300 seconds. It also showed that athletes with long experience of training and competition in cycling did not spontaneously find the most successful pacing strategy during 300 seconds. The magnitude of differences in performance between The free chosen strategy and the most optimal strategy implies that a right choice of pacing strategy can mean a difference between a gold medal and an emplacement far away from the table of winners in an Olympic Games competition. Moreover, the results indicate that it might be a difference among male and female athletes regarding correlation between mean power and accumulated oxygen deficit which could indicate that it is not automatically appropriate to apply a pacing strategy on female subjects that has been successful for male subjects. The mean power performed at 30 seconds did not differ significantly among the free chosen and the all-out strategy. Therefore it might be justifiable when performing the Wingate-test to use both the all-out and the free chosen strategy to secure that the subjects really achieve maximum anaerobic capacity. Finally, the study demonstrated that during 300s effort a high initial power output resulted in accelerated oxygen kinetics. However, high initial power output also resulted in higher oxygen cost of work during the last stage, which was devastating for the performance.